Kronika - CPH 27(2) (Czasopismo Prawno-Historyczne, 1975)
Kronika CPH 27(2) Materiały nadesłali E. Bagieńska, T. Fijałkowski, Z. Kaczmarczyk, H. Kupiszewski, B. Leśnodorski, Μ. Maciejewski, H. Olszewski, A. Partyka, Μ. Sczaniecki, W. Uruszczak, J. Wąsicki, H. Wolan